An ounce of prevention is worth a pound of cure—the arts as a vehicle for knowledge translation and exchange (KTE) in public health during a pandemic: a realist-informed developmental evaluation research protocol. Issue 9 (19th September 2022) - Bergeron, Dave A; Rey, Lynda; Murillo Salazar, Fernando; Michaud, Anne Marie; Ccaniahuire Laura, Felipe
Abstract : Introduction: The COVID-19 crisis has led to the adoption of strict and coercive preventive measures. The implementation of these measures has generated negative impacts for many communities. The situation is especially worrisome for Indigenous communities in Peru. Therefore, it is necessary to recognise the contribution of the experiential knowledge of Indigenous communities and to implement innovative approaches. The use of art can be a promising avenue for working in partnership with Indigenous communities. The goal of this research is to (1) develop an intervention promoting barrier measures and vaccination to limit the transmission of COVID-19 among Indigenous communities using an arts-based and community-based knowledge translation and exchange (ACKTE) model; and (2) understand the contextual elements and mechanisms associated with the process of developing a preventive intervention using the ACKTE model. Methodology and analysis: This research will take place in Indigenous communities in Peru and will be based on a developmental evaluation guided by the principles of realist evaluation. Members of two Indigenous communities, local authorities, health professionals and artists will participate in the intervention development process as well as in the developmental evaluation. For data collection, we will conduct modified talking circles and semistructured individual interviews with stakeholders as well as an analysis of documents and artistic works produced. Ethics and dissemination of results: This research received the approval of the Université du Québec à Rimouski 's research ethics board. In addition to scientific articles, the results of this research will be disseminated through videos and during an artistic performance.